Penerapan minapadi untuk mendukung ketahanan pangan dalam meningkatkan kesejahteraan masyarakat Desa Koto Benai Kabupaten Kuantan Singingi - Eni Sumiarsih; Kausar Kausar; Adriman Adriman; Eddiwan Eddiwan; Ika Fitria Hasibuan (Unri Conference Series: Community Engagement, 2019)
Koto Benai village is a village where most of its inhabitants have eyes in the agricultural sector. The people of Koto Benai Village grow rice only 2 times a year. Mina padi is a way of maintaining fish between rice plants, this is one of the appropriate technologies in paddy fields. The types of fish that can be maintained on the system are carp, tilapia, tilapia, catfish, and others. The purpose of this activity is so that farmers can understand the technique of using fish with the Minapadi system. It is expected that after this service the farmers and the community can apply the Minapadi system technology to increase farmers' income which is not only from agricultural products. independent village. Method in this activity consists of lectures and direct practice in the field. The implementation of rice mina is carried out in several stages: the situation analysis stage and preliminary observations, training in the cultivation of rice mina and fish farming, mentoring and mentoring of rice mina, determining the reliability of activity indicators, and problems that arise. The results obtained from the implementation of this activity were enthusiastic communities to carry out minapadi cultivation, agricultural and livestock production increased in 24%.